Percepção Ambiental em Museus Paisagens de Arte Contemporânea: a legibilidade dos museus Inhotim/Brasil e em Serralves/Portugal avaliada pelo público/visitante - Costa, Robson Xavier da (2014)
This thesis nalyzes the wayfinding in Landscape Museum of Contemporary Art (MPAC), based on the Institute of Contemporary Art CACI, Minas Gerais, Brazil and the Museum of Contemporary Art of the Serralves Foundation, Porto, Portugal. The study focuses on the interrelationship of the public/visitors with the landscape, architecture and contemporary art museums in these, in order to understand visual perception and apprehension of such an environment for their users. For both were confronted documentation (visual and written) and people talk. The main hypothesis put forward is that the audience/visitor MPAC appreciates the interrelationship between the natural environment (park/garden) and built environment (the works of contemporary art and the galleries), giving equal value to both. To complement this, a second hypothesis is that during the visit to MPACS, visitors define their paths spontaneously, but strongly influenced by existing visual indicators (maps, signage and striking landscape elements), which facilitate the readability of space, which also contribute to the offered services and the experiences of similar institutions. The analytical basis of the research used the concepts of legibility (LYNCH, 2009), wayfinding (GIBSON, 2009; ARTHUR, PASSINI, 2002; WEISMAN, 1982), Experiential Cotinnum (TUAN, 1985), Space Bound (CRUZ PINTO, 2007) and habitus (BOURDIEU, 1992). Methodologically was used qualitative research (DEMO 2000) by means of a case study (YIN, 2005; STAKE, 1999) and participant observation (WHYTE, 2005). In the two institutions interviews with researchers and curators, behavior observation and questionnaires from employees, trainees, monitors and the public/visitor of the two museums were performed. Although partially referende the initial hypothesis, the research showed that the public/visitor value appears more natural environments, they experience a greater intensity and in addition to the factors listed in the second case, your perception and definition of paths suffer significant influence of emotional relations established with space. Generally the audience/visitor adapts easily to different demands of contemporary art exhibition in the two museums and the built environment (park/garden and museum) interferes with your reading path during the visit, perceived by the public/visitor condition as a factor that favors the enjoyment of works on different mounts (wayfinding), though often become a factor that hinders the legibility of the building and its built environment